16S Metagenomics Of Branch-Leaf Compost At The Expo Memorial Park Osaka: 16S Metagenomik Kompos Cabang-Daun Di The Expo Memorial Park Osaka - Fera Aulia; Risma Wiharyanti (Journal of Multidisciplinary Science, 2023)
Compost is one of the potential microbial habitats for the discovery of a wide range of novel biocatalysts. Compost sample originally made of plant litter, were collected at the Expo Park (Osaka, Japan). The temperature of composts is around 50 °C. Metagenomic DNA was isolated from compost and was used to amplify partial 16S rRNA genes (rDNAs) by polymerase chain reaction for investigation of the microbial diversity in the compost. Molecular microbial identification was carried out by metagenome analysis of 16S rRNA using MinION Next Generation Sequencing (NGS). The results indicated that branch-leaf compost sample from Expo Park is dominated by thermophilic microorganism. The majority of bacteria are Caldicoprobacter, Hungateiclostridium, and Thermoclostridium. To conclude, thermophilic microorganism is not only found in extreme environment, they also presence even in moderate temperature.